ANALISIS KEMAMPUAN CALON GURU DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN - Jadidah, Ines Tasya; Awalia, Eby Sania; Abdillah, Althaafi; Ananta, Selvia; Darmawan, Naufal (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2022)
The purpose of this study was conducted in order to analyze the ability of prospective teachers in developing learning media. This research uses descriptive qualitative research whose instrument is observation to obtain information about the problem. The result of the interview is that most prospective teachers will feel comfortable to always use learning media in their teaching and learning activities if it is necessary and possible. The development of the times will also develop learning media for students, at this time the learning media is very innovative especially for the next few years. This is based on the results of research conducted through interviews by researchers, where the interviewees are prospective educators who will devote themselves to educating new generations in the next few years. From the results of interviews with several sources, they agree that learning media must be creative and innovative, especially for the current digital age, it is clear that educators must be even more creative and innovative in developing fun learning media so that they can attract students' interest in learning regardless of what media will be used, be it simple media or electronic media